Priority Factors for Community Participation in the Planning Stage of Neighborhood Upgrading Shelter and Sector Project in Bandar Lampung - Balqis Febriyantina Gunari; Citra Persada; Zulqadri Ansar (The Indonesian Journal of Planning and Development, 2017)
The purpose of this research is to identify priority factors for community participation in the planning stage of Neighborhood Upgrading Shelter and Sector Project (NUSSP) in Bandar Lampung. The analytical method used is Analytical Hierarchy Process (AHP) to obtain the priority factors gathered from nine key informants, and factor analysis method to analyze data taken from 101 participating communities in Kota Karang settlement as the case. The result shows that the priority factors causing community participation are: 1) a good cooperation among the key stakeholders involving the local government, the village head, the chairman of the neighborhood association, the community’s public figures, and non-governmental organization (NGO) represented in the community self-reliance organization (Lembaga Keswadayaan Masyarakat/LKM); 2) community inclusion by the NGO In the LKM; 3) community’s cooperative behaviour in the neighborhood; 4) clarity of the program socialization by the local government with an easy-to-understand language; 5) the low-income community in decent life; 6) proper acknowledgement to community opinion; 7) community freedom to speak in the public meeting.